Differential Cytotoxicity Responses by Dog and Rat Hepatocytes to Phospholipogenic Treatments - James K. Morelli; Paul J. Ciaccio (Journal of Toxicology)
Dog and rat hepatocytes were treated with phospholipogenics to identify the more sensitive species and to determine whether lysosomal or mitochondrial changes were the primary cause of cytotoxicity. Endpoints included cell death, lysosome membrane integrity, mitochondrial membrane polarization, and fluorescent phospholipid (NBD-PE). Dog cells exhibited lower survival IC50 values than did rat cells with all phospholipogenic treatments and exhibited a lower capacity to accumulate NBD-PE in 4 of 5 phospholipogenic test conditions. The lysosomal modulator Bafilomycin A1 (Baf) rescued dog cells from cytotoxicity caused by 3 phospholipogenic 5HT1b antagonists and hydroxychloroquine, but not fluoxetine, and rescued rat cells from hydroxychloroquine and NMTMB, a 5HT1b antagonist. Following NMTMB treatment, rat mitochondrial membrane hyperpolarization was observed at modestly cytotoxic concentrations and depolarization at the highest concentration. At the highest test concentration, lysosomal loss of acridine orange occurred by 30 min, mitochondrial polarity changes by 1 hr, and NBD-PE accumulation by 2 hr, respectively. Baf shifted mitochondrial polarity from a depolarized state to a hyperpolarized state. These data demonstrate that (a) dog hepatocytes were generally less capable of mounting an adaptive, protective phospholipidotic response than rat hepatocytes, (b) effects on mitochondria and survival were preventable by lysosomal protection, and (c) destabilizing changes in both organelles are involved causally in cytotoxicity.